2019
DOI: 10.1136/jnnp-2019-320912
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of anti-inflammatory agents for the treatment of major depressive disorder: a systematic review and meta-analysis of randomised controlled trials

Abstract: ObjectivesTo systematically review the efficacy and safety of anti-inflammatory agents for patients with major depressive disorders.MethodsWe searched the literature to identify potentially relevant randomised controlled trials (RCTs) up to 1 January 2019. The primary outcome was efficacy, measured by mean changes in depression score from baseline to endpoint. Secondary outcomes included response and remission rates and quality of life (QoL). Safety was evaluated by incidence of classified adverse events. Hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
128
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(135 citation statements)
references
References 44 publications
5
128
1
1
Order By: Relevance
“…In contrast, although non-aspirin NSAIDs have mixed selectivity, they are mostly selective for COX-2 inhibition or non-selective, possibly leading to the observed harmful effect of non-aspirin NSAIDs on these psychiatric disorders. This was however partly inconsistent with the findings of a recent meta-analysis that found celecoxib to have an antidepressant effect when added to traditional antidepressants [24]. One possible explanation for the contradictory findings might be the fact that we studied newly onset depression, anxiety, and stress-related disorders after cancer diagnosis whereas Bai et al studied the treatment effort on prevalent depression [24].…”
Section: Discussioncontrasting
confidence: 78%
“…In contrast, although non-aspirin NSAIDs have mixed selectivity, they are mostly selective for COX-2 inhibition or non-selective, possibly leading to the observed harmful effect of non-aspirin NSAIDs on these psychiatric disorders. This was however partly inconsistent with the findings of a recent meta-analysis that found celecoxib to have an antidepressant effect when added to traditional antidepressants [24]. One possible explanation for the contradictory findings might be the fact that we studied newly onset depression, anxiety, and stress-related disorders after cancer diagnosis whereas Bai et al studied the treatment effort on prevalent depression [24].…”
Section: Discussioncontrasting
confidence: 78%
“…The evidence supporting this hypothesis has motivated a search for biomarkers of immune status that could be used to stratify MDD cases and to predict therapeutic response to anti-inflammatory drugs (2,4). Anti-inflammatory drugs have been associated with antidepressant effects in clinical trials for depression (5), in planned post hoc analysis of a subgroup of patients with MDD defined by a blood protein biomarker (6), and in clinical trials for arthritis and other systemic inflammatory or autoimmune disorders often associated with comorbid depression (7)(8)(9). It is already clear that to optimize the potential of anti-inflammatory interventions for depressive symptoms, new therapeutics must be precisely guided by development of immune biomarkers and companion diagnostics (4).…”
mentioning
confidence: 99%
“…A systematic review of 30 randomised controlled trials (RCTs) showed that NSAIDs alleviated symptoms of depression [standard mean difference (SMD) -0.55, 95% CI -0.75 to -0.35] compared to the placebo arm [77]. A negative association between long-term NSAID use and depression [HR (95% CI): 0.20 (0.04-0.87)] but a non-specific statistical correlation on repeated testing is seen [78].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%